Pedagogical Principles of Military Administration During the Reign of the Mangit Dynasty (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article cites the pedagogical aspects of military rule during the reign of the Mangyts.